Trimetazidine therapy for diabetic mouse hearts subjected to ex vivo acute heart failure. - Emilene Breedt; Lydia Lacerda; M Faadiel Essop (PLoS ONE)
Acute heart failure (AHF) is the most common primary diagnosis for hospitalized heart diseases in Africa. As increased fatty acid β-oxidation (FAO) during heart failure triggers detrimental effects on the myocardium, we hypothesized that trimetazidine (TMZ) (partial FAO inhibitor) offers cardioprotection under normal and obese-related diabetic conditions. Hearts were isolated from 12-14-week-old obese male and female diabetic (db/db) mice versus lean non-diabetic littermates (db/+) controls. The Langendorff retrograde isolated heart perfusion system was employed to establish an ex vivo AHF model: a) Stabilization phase-Krebs Henseleit buffer (10 mM glucose) at 100 mmHg (25 min); b) Critical Acute Heart Failure (CAHF) phase-(1.2 mM palmitic acid, 2.5 mM glucose) at 20 mmHg (25 min); and c) Recovery Acute Heart Failure phase (RAHF)-(1.2 mM palmitic acid, 10 mM glucose) at 100 mmHg (25 min). Treated groups received 5 μM TMZ in the perfusate during either the CAHF or RAHF stage for the full duration of each respective phase. Both lean and obese males benefited from TMZ treatment administered during the RAHF phase. Sex differences were observed only in lean groups where the phases of the estrous cycle influenced therapy; only the lean follicular female group responded to TMZ treatment during the CAHF phase. Lean luteal females rather displayed an inherent cardioprotection (without treatments) that was lost with obesity. However, TMZ treatment initiated during RAHF was beneficial for obese luteal females. TMZ treatment triggered significant recovery for male and obese female hearts when administered during RAHF. There were no differences between lean and obese male hearts, while lean females displayed a functional recovery advantage over lean males. Thus TMZ emerges as a worthy therapeutic target to consider for AHF treatment in normal and obese-diabetic individuals (for both sexes), but only when administered during the recovery phase and not during the very acute stages.